Activation of Human CD11b+ B1 B-Cells by Trypanosoma cruzi-Derived Proteins Is Associated With Protective Immune Response in Human Chagas Disease - Passos, Livia Silva Araújo; Magalhães, Luísa Mourão Dias; Soares, Rodrigo Pinto; Marques, Alexandre F.; Alves, Marina Luiza Rodrigues; Giunchetti, Rodolfo Cordeiro; Nunes, Maria do Carmo Pereira; Gollob, Kenneth J.; Dutra, Walderez Ornelas (Frontiers in Immunology, 2019)
B-cells mediate humoral adaptive immune response via the production of antibodies and cytokines, and by inducing T-cell activation. These functions can be attributed to distinct B-cell subpopulations. Infection with Trypanosoma cruzi, the causative agent of Chagas disease, induces a polyclonal B-cell activation and lytic antibody production, critical for controlling parasitemia. Individuals within the chronic phase of Chagas disease may remain in an asymptomatic form (indeterminate), or develop severe cardiomyopathy (cardiac form) that can lead to death. Currently, there is no effective vaccine to prevent Chagas disease, and no treatment to halt the development of the cardiomyopathy once it is installed. The pathology associated with cardiac Chagas disease is a result of an inflammatory reaction. Thus, discovering characteristics of the host’s immune response that favor the maintenance of favorable heart function may unveil important immunotherapeutic targets. Given the importance of B cells in antibody production and parasite control, we investigated T. cruzi-derived antigenic fractions responsible for B-cell activation and whether frequencies and functional characteristics of B-cell subpopulations are associated with different clinical outcomes of human Chagas disease. We stimulated cells from indeterminate (I) and cardiac (C) Chagas patients, and non-infected individuals (NI), with T. cruzi-derived protein- (PRO), glycolipid- (GCL) and lipid (LIP)-enriched fractions and determined functional characteristics of B-cell subpopulations. Our results showed that the frequency of B-cells was similar amongst groups. PRO, but not GCL nor LIP, led to an increased frequency of B1 B-cells in I, but not C nor NI. Although stimulation with PRO induced higher TNF expression by B1 B-cells from C and I, as compared to NI, it induced expression of IL-10 in cells from I, but not C. Stimulation with PRO induced an increased frequency of the CD11b+ B1 B-cell subpopulation, which was associated with better cardiac function. Chagas patients displayed increased IgM production, and activation of gamma-delta T-cells, which have been associated with B1 B-cell function. Our data showed that PRO activates CD11b+ B1 B-cells, and that this activation is associated with a beneficial clinical status. These findings may have implications in designing new strategies focusing on B-cell activation to prevent Chagas disease cardiomyopathy.